Adsorption isotherms and kinetic studies of nitrogen-doped porous carbon by sodium amide activation from natural rubber for CO2 capture - Nurfarhana, M.M.; Asikin-Mijan, N.; Yusoff, Siti Fairus M.; Abdulkareem-Alsultan, G.; Othman, M.A.R.; Kawi, Sibudjing (Elsevier, 2025)
This study seeks to provide straightforward and renewable nitrogen-doped porous carbonaceous adsorbents with superior carbon dioxide (CO2) adsorption capabilities. Nitrogen-enriched porous carbons were synthesised using a single-step sodium amide activation of carbonized natural rubber. The activation temperature of the adsorbent (400–600 °C) and the AC/NaNH2 ratios (1:1–1:4) were applied to optimize the pore shape and nitrogen concentration for enhanced CO2 adsorption performance. The optimal sample, NRAC-NaNH2-600-2, had the maximum CO2 adsorption capacity of 2.95 mmol/g at 25 °C and 1 bar. The ideal sample demonstrated reusability for up to 8 consecutive cycles, exhibiting remarkable stability with only a 5.5 % in adsorption capacity compared to the initial. Two parameters were identified: specific surface area and nitrogen content, which significantly influence the CO2 adsorption capability of these adsorbents. The CO2 adsorption isotherm at 25 °C was evaluated using the Freundlich isotherm model, which exhibited the best fit (R2 = 0.9856), indicating multilayer adsorption on a heterogeneous surface. Additionally, the adsorption kinetic data were well fitted to the pseudo-first-order kinetic which deduce physical adsorption dominated during the CO2 loading. This research may foster novel concepts for nitrogen-doped adsorbents characterized by low activation temperatures, renewable precursors as a potential CO2 adsorption material.